ANNOUNCEMENT-ANNOTATION TEXTS: DEFINITION, CORRELATION AND SYNTHESIS - Olga Dzykovych; Sandra J. Langer (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The paper deals with the problems of definition, correlation and synthesis of two text types: announcement and annotation. The main goal of this article is to postulate they have enough similar features to be combined in one text type. The examination of the relationship between different types of text is one of the most current research topics in the European linguistic literature, to which more and more studies draw the attention. However, the empirical research is still rarely carried out. In this paper, announcement and annotation have been examined on common and different features of both speech genres with a view to a correlation of these genres. After the synthesis of two text types, the authors determined their common traits which evidence these genres consistency. After all, the suggestion was made to integrate the definitions of announcement and annotation texts into one definition: announcement-annotation texts (or annotexts). Although this postulate needs to be modified and supplemented in view of text types selected for analysis, it is a good starting point for further research.